The utilization of the human thinking representation oriented model (MORPH) for the establishment of a fluvial sensitivity index (FSI): A proposed contribution to the environmental sensitivity to oil classification - Costa, Daiana Marques [UNESP]; Riedel, Paulina Setti [UNESP]; da Cunha, Cenira Maria Lupinacci [UNESP]; Zambon, Antonio Carlos (Universidade Federal do Rio Grande do Sul, 2015)
This paper presents the using of the Human Thinking Representation Oriented Model (MORPH) as analysis tool as support to the creation of a classification system, that aims to determine the environmental sensitivity to oil in waterways, based on the main classification system by the National Oceanic and Atmospheric Administration (NOAA) and by the Petrobras S.A. to river environment. This proposal came about because of ever increasing reoccurrences of oil spills in areas on the continent, causing environmental damage to waterways and the lack of a broad classification system that meets the needs of the different environments found in waterways, once the main sensitivity studies are directed towards coastal settings. The MORPH simplified the comparison of many interdependent variables, identifying the fundamental physical parameters for establish the fluvial environments that make up the Fluvial Sensitivity Index (FSI), for instance: rocky shores, artificial structures, beaches, muddy substrate banks, point-bars, natural dikes, vegetated shores and flood plains associated with vegetation. The FSI relates the physical characteristics that influence directly natural persistence, dispersion and the cleaning and/or removal of oil conditions, which is directly reflected on the impact level.
Utilização do modelo orientado à representação do pensamento humano (MORPH) no estabelecimento do índice de sensibilidade fluvial (ISF): Uma proposta de contribuição à classificação da sensibilidade ambiental ao óleo
Keywords: Environmental sensitivity to oil mapping; Fluvial geomorphology; Fluvial sensitivity to oil; SAO maps